The Identification of The City on The Legibility and Wayfinding Concepts: A Case of Trabzon - Aysel Yavuz; Nihan Canbakal Ataoğlu; Habibe Acar (Alanya Hamdullah Emin Paşa Üniversitesi, 2020)
The concept of wayfinding includes understanding the space and finding direction within the space. But as cities and architectural spaces grow and become more complex, visitors and locals of the space can find it difficult to find direction. For these reasons, for visitors who speak different languages, along with these elements, there is a need for well-designed information and direction-finding graphics and landmarks that have a universal quality. The aim of the study is to explain the concepts of wayfinding and way-finding, defined as “direction-finding” in the literature and to create awareness. Furthermore, to analyze the concept of wayfinding and the direction designs that aim to transform the cities that have become complex into more understandable spaces, through the city of Trabzon and to examine the problems of the city in this context and to make suggestions. In this study, Trabzon will be evaluated with the concepts of legibility and directability and the direction and information designs over the focal point, regions, edges, nodes, roads with which Kevin Lynch has defined the imageable, readable city. A survey was conducted to investigate the spatial information elements and legibility of Trabzon city. Furthermore, to create awareness for other cities with similar problems.